2020
DOI: 10.1111/petr.13676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donor cause of death, ischemia time, inotrope exposure, troponin values, cardiopulmonary resuscitation, electrocardiographic and echocardiographic data on recipient outcomes: A review of the literature

Abstract: Background Heart transplantation has become standard of care for pediatric patients with either end‐stage heart failure or inoperable congenital heart defects. Despite increasing surgical complexity and overall volume, however, annual transplant rates remain largely unchanged. Data demonstrating pediatric donor heart refusal rates of 50% suggest optimizing donor utilization is critical. This review evaluated the impact of donor characteristics surrounding the time of death on pediatric heart transplant recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 89 publications
0
16
1
Order By: Relevance
“…In a recent review, McCulloch et al have suggested that keeping the ischemic time to less than 4 hours with an acknowledgement that factors other than the objective measure of time probably were important determinants of outcome. 3 In our study, the mortality at 1 year for prolonged IT group was slightly higher than the low-risk donor group. Prolonged IT group did have a significantly higher percentage of recipients who were post-congenital heart surgery which has been previously recognized as a risk factor for post-transplant mortality by itself.…”
Section: Discussionsmentioning
confidence: 40%
See 2 more Smart Citations
“…In a recent review, McCulloch et al have suggested that keeping the ischemic time to less than 4 hours with an acknowledgement that factors other than the objective measure of time probably were important determinants of outcome. 3 In our study, the mortality at 1 year for prolonged IT group was slightly higher than the low-risk donor group. Prolonged IT group did have a significantly higher percentage of recipients who were post-congenital heart surgery which has been previously recognized as a risk factor for post-transplant mortality by itself.…”
Section: Discussionsmentioning
confidence: 40%
“…[5][6][7] Similarly, the impact of reduced ejection fraction of the donor heart on graft survival is not completely clear, with studies supporting avoidance and use of reduced EF donors. 3 According to the current ISHLT statement, the effect on graft outcome does not seem to be additive when multiple risk factors were present in the same donor although this is not supported by evidence and does not translate into practice as evidenced by poor utilization of these high-risk donors. 1 Only 40% of donors with ≥1 risk factor are utilized compared to 80% with no risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of established standards or guidelines for pediatric heart assessment and subsequent acceptance may limit donor utilization with direct impact on waitlist outcomes. To address some of these issues, our center's experience prompted the development of the ISHLT pediatric consensus guidelines and the suite of papers recently published in Pediatric Transplantation 9‐17 …”
Section: Discussionmentioning
confidence: 99%
“…Among those who do survive to transplant, waitlist characteristics, including waitlist duration, available mechanical support options, and renal injury all contribute to post‐transplant outcomes 3‐8 . The waitlist phase of care has received considerable attention recently, including the recent publication of an International Society for Heart & Lung Transplantation (ISHLT) consensus statement on donor organ acceptability and other important papers 9‐19 …”
Section: Introductionmentioning
confidence: 99%